Analisis Kualitas Pelayanan Unit Usaha Simpan Pinjam Koperasi Wanita Kenanga Pontianak - Helman Fachri; Asbani A (JURNAL MANAJEMEN MOTIVASI, 2015)
This study aimed to analyze the quality of service to business unit Women's savings and credit cooperatives Kenanga Pontianak. quality dimensions studied were reliability, responsiveness, assurance, empathy and tangibles. This study using purposive sampling technique with a sample of 72 respondents out of 266 members. The analytical method used is Cartesian diagram Analysis (Importance Performance Analysis)  to determine the level of importance of service quality and customer satisfaction, and the results obtained where X = 3.88 and Y = 3.97, which means that the quality of service Unit Savings and Loans granted by Women's Cooperative Kenanga Pontianak is still not in line with expectations that members of the members are not satisfied.Based on the results of analysis of Cartesian diagram shows that there are three significant variables that three variables, namely the regularity of the work schedule is quite important by respondents with a score of 3.50 and variable 7 is the ability to serve lending is very important by respondents with a score of 3, 79. The next variable is the availability of parking space 18 received responses are less satisfied thanrespondents with a score of 3.88.